SOSIALISASI ISLAM DI JAWA ABAD KE 15-17: RADIKAL ATAU PERSUASIF? (TELAAH ATAS HISTORIOGRAFI LOKAL DAN ASIMILASI TINGGALAN ARKEOLOGIS) - Saptaningrum, Irna (Berkala Arkeologi, 2004)
On the post-modernist view that the "meaning" of an archaeological data depends on the interpretation of the interpreter to interpret it. This gap makes it possible to accommodate other views from various versions, so that there is no single interpretation. Likewise with the interpretation of the way the socialization of Islam is carried out in Java, it can be said to be radical and it can also be persuasive depending on the point of view of how one is viewed, the goals and intentions of the observer itself which also influence the "meaning" it creates.